PENGGUNAAN SPRINGATE MODEL SEBAGAI PREDIKTOR KEBANGKRUTAN PERUSAHAAN DI BURSA EFEK INDONESIA (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to determine and analyze the calculation of the Springate model in the property industry and predict which companies are in the category of potential bankruptcy. the variables used in this study are the Springate S-Score method, financial ratios and bankruptcy score results. The samples used were 6 property companies listed on the Indonesia Stock Exchange from the 2019-2021 period. This study uses the Springate S-Score analysis method which is practiced with liquidity, leverage, profitability and activity ratios. The results showed that the Springate model can be used as a predictor of corporate bankruptcy, the next result shows that bankruptcy analysis using the Springate method in the property industry shows the results that there are three companies that are declared healthy, namely PT Ciputra Surya in 2019, PT Indonesia Prima Property and PT Duta Pertiwi in 2021 with sequential S-Score values of 1.313, 0.935 and 0.867, the rest are declared as companies that have the potential for bankruptcy. The third result shows that the Working capital to total assets ratio, Net profit before interest and taxes to total assets, Net profit before interest and taxes to current liability and Sales to total assets ratio play a significant role in determining the results of the bankruptcy score in the property industry.